VP61 Patients Views Of Health Technology Assessment At The National Institute Of Health And Care Excellence (NICE): Enhancing Involvement Opportunities. (2017) - Thomas, Lizzie; Livingstone, Heidi; Leng, Gillian
Abstract : INTRODUCTION: The National Institute for Health and Care Excellence (NICE) medicines health technology assessments (HTAs) involve patients throughout (1): scoping the topic, evidence submission, attending committee as 'patient experts', consultation and appeal. A 2013 Health Select Committee report stated "It is important for the credibility of NICE and for the decisions that it makes that the patient voice is effectively and openly represented in all its work" (2). We thus wished to build on previous evaluation projects with more formal research into the views of patient organizations and individual patient experts on their involvement. We additionally sought to explore barriers to involvement. METHODS: The research was a collaboration between staff from three teams at NICE: public involvement, market research, and HTA committee support. A mix of interviews, focus groups and surveys was used to gather feedback – from patients and organizations who have engaged with NICE, but also those who had not, plus NICE committee chairs and staff. Facilitators and barriers to involvement were investigated, along with attitudes towards process and support. We used qualitative thematic analysis alongside quantitative methods. RESULTS: Key findings were that patients and patient organizations mostly: hold favourable opinions of NICE have a good understanding of process and expectations remain unsure of the impact of their inputs. Improvements identified include clarifying communications, language and roles. Plus increasing transparency of decision making and patient impact. CONCLUSIONS: The research findings and action plan, although specific to NICE, hopefully can inform others in the wider HTA ecosystem. Resources developed will be shared with Health Technology Assessment International (HTAi) networks, including updated correspondence templates and new videos explaining decision making in lay language. The research further adds to discussions around appropriate use of patient organizations scarce resources, and how best to feedback to participants and demonstrate impact of patient involvement.